A feasible way to remove the heat during adsorptive methane storage - Gütlein, Stefan; Burkard, Christoph; Zeilinger, Johannes; Niedermaier, Matthias; Klumpp, Michael; Kolb, Veronika; Jess, Andreas; Etzold, Bastian (Environmental Science & Technology, 2015)
Methane originating from biogas or natural gas is an attractive and environmentally friendly alternative to gasoline. Adsorption is seen as promising storage technology, but the heat released limits fast filling of these systems. Here a lab scale adsorptive methane storage tank, capable to study the temperature increase during fast filling, was realized. A variation of the filling time from 1 h to 31 s, showed a decrease of the storage capacity of 14% and temperature increase of 39.6 °C. The experimental data could be described in good accordance with a finite element simulation solving the transient mass, energy, and impulse balance. The simulation was further used to extrapolate temperature development in real sized car tanks and for different heat pipe scenarios, resulting in temperature rises of approximately 110 °C. It could be clearly shown, that with heat conductivity as solei mechanism the heat cannot be removed in acceptable time. By adding an outlet to the tank a feed flow cooling with methane as heat carrier was realized. This setup was proofed in simulation and lab scale experiments to be a promising technique for fast adsorbent cooling and can be crucial to leverage the full potential of adsorptive methane gas storage.
CRIS-Team Scopus Importer:2023-08-15

Comparison between phosphine and NHC-modified Pd catalysts in the telomerization of butadiene with methanol - A kinetic study combined with model-based experimental analysis - Völkl, Lisa; Recker, Sebastian; Niedermaier, Matthias; Kiermaier, Stephan; Strobel, Vinzent; Maschmeyer, Dietrich; Cole-Hamilton, David; Marquardt, Wolfgang; Wasserscheid, Peter; Haumann, Marco (Journal of Catalysis, 2015)
The telomerization of butadiene with methanol was investigated in the presence of different palladium catalysts modified either with triphenylphosphine (TPP) or 1,3-dimesityl-imidazol-2-ylidene (IMes) ligand. When pure butadiene was used as substrate, a moderate selectivity for the Pd-TPP catalyst toward the desired product 1-methoxy-2,7-octadiene (1-Mode) of around 87% was obtained, while the IMes carbene ligand almost exclusively formed 1-Mode with 97.5% selectivity. The selectivity remained unchanged when the pure butadiene feed was replaced by synthetic crack-C-4 (sCC(4)), a technical feed of 45 mol% butadiene and 55 mol% inerts (butenes and butanes). The TPP-modified catalyst showed a lower reaction rate, which was attributed to the expected dilution effect caused by the inerts. Surprisingly, the IMes-modified catalyst showed a higher rate with sCC(4) compared to the pure feed. By means of a model-based experimental analysis, kinetic rate equations could be derived. The kinetic modeling supports the assumption that the two catalyst systems follow different kinetic rate equations. For the Pd-TPP catalyst, the reaction kinetics were related to the Jolly mechanism. In contrast, the Jolly mechanism had to be adapted for the Pd-IMes catalyst as the impact of the base seems to differ strongly from that for the Pd-TPP catalyst. The Pd-IMes system was found to be zero order in butadiene at moderate to high butadiene concentrations and first order in base while the nucleophilicity of the base is influenced by the methanol amount resulting in a negative reaction order for methanol. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Telomerization; NHC ligand; TPP ligand; Palladium; Reaction kinetics; Model-based kinetic analysis